A Ballistics Study of the Winchester Supreme Elite PDX1 Ammunition. Issue 2 (June 2013) - Lapham-Simpson, Courtney; Lebaron, Ryan C.; Haag, Mike; Hatch, Gary; Nolte, Kurt B.
The Winchester Supreme Elite PDX1 .410 gauge shotgun ammunition for the Taurus Judge revolver is uniquely comprised of three copper-plated discs, 12 copper-plated BB shot pellets and a plastic shot cup. To evaluate potential wounding patterns, we characterized superficial impact, penetration, and penetration with an intermediate target. Surface patterns were assessed with foam core boards. Penetration was assessed using gelatin blocks. Penetration with an intermediate target was assessed using gelatin blocks covered by a povidone-iodine soaked shirt. All blocks were radiographed and scanned by computed tomography (CT). At increasing muzzle-to-target distances, the overall projectile spread pattern increased. There was consistent separation of the three copper-plated discs at distances beyond six feet. Discs remained centrally located with the pellets spread peripherally, in a circular pattern. This pattern persisted in the penetration tests, with the discs penetrating deeper than the pellets. Radio-opaque clothing fragments were identified both superficially and deep within the gelatin blocks. Rifling conferred stability to the coaxially aligned discs and imparted centrifugal forces to the non-aligned pellets resulting in the surface and gelatin patterns. The combination of surface and radiographic findings should allow a forensic pathologist to suspect this ammunition prior to dissection. Wounds created by this ammunition in living patients might require extensive debridement to avoid abscess formation and foreign body reactions.